A BIOCHEMICAL AND HISTOCHEMICAL STUDY OF GLUTAMIC OXALACETIC TRANSAMINASE ACTIVITY OF RAT HEPATIC MITOCHONDRIA FIXED IN SITU AND IN VITRO - Lee, Sin Hang (The Rockefeller University Press, 1968)
Rat liver perfused in situ briefly with a glutaraldehyde-formaldehyde mixture was homogenized in isotonic sucrose. The mitochondria, isolated from a homogenate of the perfused liver by differential centrifugation, assumed a slender and compact appearance similar to those often seen in an intact cell. The glutamic oxalacetic transaminase (GOT) activity of this mitochondrial fraction survived an additional formaldehyde fixation and was studied by biochemical and histochemical methods. The biochemical assay of the enzyme activity revealed that the activity was only slightly less than that of an unfixed mitochondrial fraction. The reaction product due to mitochondrial GOT activity was found to be localized to the cristae, as had been demonstrated in an intact liver cell. GOT activity of the mitochondrial fraction isolated from fresh liver tissue homogenate in 0.25 M sucrose was inactivated readily by either glutaraldehyde or formaldehyde and was no longer demonstrable by biochemical and histochemical methods after fixation.